Os cursos de Pós-Graduação Lato Sensu em Educação Infantil na Bahia: políticas e práticas da universidade pública - OLIVEIRA, Anatália Dejane Silva de (2012)
This study is integrated to research line of teacher Education and Professionalization of the College of Education, Federal University of Goiás, developed by the Nucleus of Studies and Research of Infancy and Infant Education in Different Contexts. It was investigated the Infant Education, at post graduation courses, Lato Sensu, aiming at analyzing the political nature and the social function of Infant Education at post graduated level of three different universities from the public sector in Bahia. The major assumption underlying this research is that Infant Education at this type of course understands continuing education if it creates the means of a specific training based on a critical and political approach from the process of production condition and of the teacher s work. The investigation was based on the historical and dialectical materialism as a method of knowledge production (MARX, 1977; BARBOSA, 1991, 2004, 2006; SAVIANI, 2008; KUENZER, 2008; KOSIK, 1976). The instruments to gather data were: bibliographic research, document analyses, interviews and questionnaires. During the complex task of analyzing, explaining and exposing, we work with the articulation between three methodological categories (praxis, contradiction and totality) and three conceptual (teacher education, specific education and infant education) it was prioritized the unveiling of relations in the totality of the social reality, identifying and recognizing the contradiction processes which generated and produced changing results in the constitution of historicity, on the political nature and on the social function of Infant Education, at post graduation courses, Lato Sensu. In this movement, we learnt the conceptions and senses attributed to these. It was captured both the movement of the courses, their particularities in the field of teacher education of Infant Education at post graduated level. The present study revealed that Infant Education, at post graduation courses, Lato Sensu, offered by public institutions in Bahia is a relevant locus of teacher formation associated to Brazilian educational policies. However, they were not in specific continuing education provided that the movement of the processes of production condition and of the teacher s work address childhood, children and Infant Education as a political and epistemological component of the course.